The encyclopedia of arthritis - Taylor, Guy; Stein, C. Michael [ (Carsten Michael)] , 1967- (Facts on File library of health and living, 2011)
The Encyclopedia of Arthritis, Second Edition is a complete guide to specific types of arthritis and their symptoms, causes, and diagnoses. This comprehensive resource explores the medications, pain management, and possible treatments, as well as risk factors and preventive measures that can help limit the impact of arthritis. It has been fully updated and expanded to reflect the most current information, such as the withdrawal of some arthritis drugs from use, as well as cutting-edge research, including the potential for new biological treatments. Appendixes provide information about diagnostic tests and drugs used to treat arthritis. Key topics include: Arthroscopy and arthroscopic surgery Bursitis Chronic fatigue syndrome Diet and exercise Juvenile idiopathic arthritis Physical therapy Rheumatoid arthritis Soft tissue arthritis-related problems Systemic lupus erythematosus Viral arthritis